Hand free set 01B-fon for motorbike - Ibrahim, Kisai (1997)
The use of hand free set handphone enables the driver to communicate with the caller without holding the handphone itself. However, this is not possible for motorcycle riders since there is no such hand free kit in the market. They have to pull-over and take off the helmet in order to respond to in coming call. Nevertheless, the riders could not find the right and safe spot to stop by, due to heavy traffic. This project research is to design a kit that can be used by motorcycle riders. The "Hand Free Set 01 B-FON" is designed especially for the motorcycle riders to communicate using the handphone while riding.